2019
DOI: 10.1029/2019gc008374
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Compositions of Sulfides in Exhumed High‐Pressure Terranes: Implications for Sulfur Cycling in Subduction Zones

Abstract: Subduction is a key component of Earth's long‐term sulfur cycle; however, the mechanisms that drive sulfur from subducting slabs remain elusive. Isotopes are a sensitive indicator of the speciation of sulfur in fluids, sulfide dissolution‐precipitation reactions, and inferring fluid sources. To investigate these processes, we report δ34S values determined by secondary ion mass spectroscopy in sulfides from a global suite of exhumed high‐pressure rocks. Sulfides are classified into two petrogenetic groups: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 283 publications
(274 reference statements)
2
29
0
Order By: Relevance
“…4a; Supplementary Table 1), and previous experimental results 11 . If slab fluids are dominated by sulfate as some recent studies propose 13 , several predictions follow. First, the oxidizing fluid will produce a redox gradient in the immediate wallrock, but this is not recorded in the selvages we examined.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…4a; Supplementary Table 1), and previous experimental results 11 . If slab fluids are dominated by sulfate as some recent studies propose 13 , several predictions follow. First, the oxidizing fluid will produce a redox gradient in the immediate wallrock, but this is not recorded in the selvages we examined.…”
Section: Discussionmentioning
confidence: 92%
“…3) are similar to their protoliths, the young marine sedimentary rocks (Phanerozoic) that mostly have δ 34 S values of −24 to −8‰ due to the presence of biogenically produced sulfide 19,44 . It is suggested that sulfide in sediments retains its δ 34 S characteristics during subduction metamorphism 13 and that metasediments may act as a negative δ 34 S reservior in subducting slabs. The vein pyrite core with negative δ 34 S (−8‰) in sample L1013 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations